Protective effects of Cassia tora leaves in experimental cataract by modulating intracellular communication, membrane co-transporters, energy metabolism and the ubiquitin-proteasome pathway. (1st January 2017) - Sreelakshmi, V.; Abraham, Annie
Abstract: Context: Cataract is the clouding of eye lens which causes impairment in vision and accounts for the leading factor of global blindness. Functional food-based prevention of cataract finds application in vision research because of its availability and easy access to all classes of the society. Cassia tora Linn. (Caesalpinaceae) is an edible plant mentioned in the traditional systems of medicine for whole body health, especially to the eyes. Objective: The present study evaluates the potential of ethyl acetate fraction of Cassia tora leaves (ECT) on experimental cataract. Materials and methods: Cataract was induced by a single subcutaneous injection of sodium selenite (4 μg/g body weight) on 10th day. ECT was supplemented orally from 8th day up to 12th day at a concentration of 5 μg/g body weight and marker parameters were evaluated after 30 days. Results: The production of MPO and the activation of calpain were reduced 52.17% and 36.67% by ECT in lens tissue, respectively. It modulated the energy status by significantly increasing the activity of CCO 1 (55.56%) and ATP production (41.88%). ECT maintained the ionic balance in the lens by reducing the level of sodium (50%) and increasing the level of potassium (42.5%). It also reduced cell junction modifications and preserved a functional ubiquitin-proteasome pathway. Discussion and conclusion: The results reinforce the growing attention on wild plant food resources for preventive protection against cataract. The data suggest the value of Cassia tora leaves as a functional food for ameliorating cataract pathology.